2014
DOI: 10.1007/s11684-015-0375-1
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid inducers of Nrf2 signaling as potential therapeutic agents in sickle cell disease: a review

Abstract: Sickle cell disease (SCD) is an inherited disorder of hemoglobin in which the abnormal hemoglobin S polymerizes when deoxygenated. This polymerization of hemoglobin S not only results in hemolysis and vasoocclusion but also precipitates inflammation, oxidative stress and chronic organ dysfunction. Oxidative stress is increasingly recognized as an important intermediate in these pathophysiological processes and is therefore an important target for therapeutic intervention. The transcription factor nuclear eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…Oxidative stress and inflammation play a major role in the pathophysiology of SCD, so drugs that induce HbF and reduce oxidative stress have greater clinical efficacy [29,50,51,52]. There is mounting evidence that treatment with NRF2 activators in SCD mice reduces oxidative stress while inducing HbF [23,24,29,30,40].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation play a major role in the pathophysiology of SCD, so drugs that induce HbF and reduce oxidative stress have greater clinical efficacy [29,50,51,52]. There is mounting evidence that treatment with NRF2 activators in SCD mice reduces oxidative stress while inducing HbF [23,24,29,30,40].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that naturally occurring triterpenoids affect Nrf2/ARE pathway and its downstream targets by triterpenoids were shown to be protective in different diseases [ 173 , 174 , 175 ]. Furthermore, Nrf2 activation and subsequent regulation of the transcription of the plethora of protective genes may be increased due to the chemical modifications of the triterpenoid structure [ 173 ].…”
Section: Oxidative Stress and Transcription Factorsmentioning
confidence: 99%
“…Activation of Nrf2 with dimethylfumarate (DMF), enhances antioxidant defenses, and inhibits inflammation and vaso-occlusion in SCD mice, also in an HO-1-dependent manner [312]. Triterpenoids have been suggested as a potential approach for SCD and synthetic oleanane (derived from oleanolic acid) triterpenoids (SOTs) are known to exert anti-inflammatory effects through Nrf2 activation, leading to transcription of enzymes, including HO-1 [430].…”
Section: Anti-inflammatory Therapeutic Approaches For Scdmentioning
confidence: 99%